2022
DOI: 10.1542/peds.2021-056164
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and the Risk of SARS-CoV-2 Infection Among Children and Adolescents

Abstract: OBJECTIVE Over 6 million pediatric SARS-CoV-2 infections have occurred in the United States, but risk factors for infection remain poorly defined. We sought to evaluate the association between asthma and SARS-CoV-2 infection risk among children. METHODS We conducted a retrospective cohort study of children 5 to 17 years of age receiving care through the Duke University Health System and who had a Durham County, NC residential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 35 publications
2
24
0
2
Order By: Relevance
“…Such improved asthma control, probably due to reduced exposure to asthma triggers and increased treatment adherence, led by the fear of COVID-19, points out that asthma was not a risk factor for severe COVID-19. In keeping with this, a retrospective cohort study [ 12 ] in North Carolina found no evidence that asthma predisposes children to SARS-CoV-2 infection or severe illness from COVID-19. However, the level of asthma control is a key factor with respect to the risk of severe COVID-19.…”
Section: Children With Cld and Risk For Severe Covid-19mentioning
confidence: 83%
“…Such improved asthma control, probably due to reduced exposure to asthma triggers and increased treatment adherence, led by the fear of COVID-19, points out that asthma was not a risk factor for severe COVID-19. In keeping with this, a retrospective cohort study [ 12 ] in North Carolina found no evidence that asthma predisposes children to SARS-CoV-2 infection or severe illness from COVID-19. However, the level of asthma control is a key factor with respect to the risk of severe COVID-19.…”
Section: Children With Cld and Risk For Severe Covid-19mentioning
confidence: 83%
“…Table 1 shows that there were 716,690 children and young adults aged �25 years old with prevalent asthma in Ontario in 2019. Of these, 7.1% were pre-schoolers (0-4 years), 16.4% early school aged (5-9), 21.4% early teens (10)(11)(12)(13)(14), and 55.1% youths and young adults (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The study cohort consisted of 41.9% females, largely from areas of middle to high income quintiles (63.4%), and the majority (92.5%) resided in urban areas.…”
Section: Population Characteristicsmentioning
confidence: 99%
“…There is limited literature examining the impact of the COVID-19 pandemic in children and young adults with asthma. While recent literature suggests improved asthma control during the pandemic, it has reported mixed results on whether individuals with asthma have greater susceptibility to COVID-19 [9][10][11][12]. Understanding how the pandemic has impacted asthma-related HSU and medication use, can provide insights into medication adherence, asthma symptom and exacerbation control during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…For citation: Zdorov'e Rebenka. 2022;17 (2):107-113. doi: 10.22141/2224-0551.17. 2.2022.1503 Резюме.…”
Section: нові погляди на діагностику та лікування бронхіальної астми ...unclassified
“…Серед 12 648 дітей 706 (5,6 %) мали позитивний результат на інфекцію SARS-CoV-2, у тому числі 350 (2,8 %) дітей з астмою та 356 (2,8 %) дітей без астми (ВШ 0,98; 95% ДІ 0,85-1,13). Не було доказів змін цього зв'язку при призначенні інгаляційних кортикостероїдів, тяжкому загостренні в анамнезі або супутніх атопічних захворюваннях [14].…”
Section: бронхіальна астма та коронавірусна хвороба (Covid-19)unclassified